COMBINING ABILITY STUDIES FOR QUANTITATIVE TRAITS IN BRASSICA JUNCEA - N. Ali; N. U. Khan; S. Ali; Farhatullah; S. Gul; M. Saeed; K. Naveed (Journal of Animal and Plant Sciences, 2015)
Combining ability was determined in an 8 × 8 F1 diallel cross of Brassica juncea L. genotypes for various quantitative traits during 2010-2011 at the University of Agriculture, Peshawar, Pakistan. Genotypes revealed highly significant (p≤0.01) differences for days to maturity, plant height, primary branches plant-1, pods main raceme-1 and seed yield plant-1 while significant (p≤0.05) variations were noted for days to 50% flowering. According to combining ability analysis, mean squares due to general combining ability (GCA) were significant (p≤0.01) for all the traits except days to 50% flowering and maturity. Mean squares due to specific combining ability (SCA) and reciprocal combining ability (RCA) were significant (p≤0.01) for all the traits except SCA mean squares for seed yield plant-1. Mean squares due to RCA were even greater than GCA/SCA for some variables, and therefore maternal effects cannot be ignored. The variations among genotypes for earliness and plant height were controlled by non-additive gene action, while morphological and seed yield traits were governed by additive gene action. Genotypes MYT120, MYT124 and MYT105 and F1 hybrids MYT117 × MYT123, MYT103 ×  MYT124, MYT009 × MYT123,  MYT123 ×  MYT009 and MYT117 × MYT113 were identified as best general and specific combiners and could be exploited through selection in early segregating populations. Results suggested the use of integrated breeding strategies which can efficiently utilize the additive as well as non-additive genetic variations.
Keywords: Brassica juncea L.; combining ability; diallel analysis; general and specific combining ability; quantitative traits